Match and manage - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The 17th World Congress of Soil Science, to be held from 14 to 21 August 2002 in Thailand, will focus on indigenous and scientific knowledge systems. (Note: the 18th conference will be in 2006, in Philadelphia, USA).WCSS officeKasetsart University,...